2015
DOI: 10.1103/physrevlett.114.125002
|View full text |Cite
|
Sign up to set email alerts
|

Strong Ionization Asymmetry in a Geometrically Symmetric Radio Frequency Capacitively Coupled Plasma Induced by Sawtooth Voltage Waveforms

Abstract: The ionization dynamics in geometrically symmetric parallel plate capacitively coupled plasmas driven by radio frequency tailored voltage waveforms is investigated using phase resolved optical emission spectroscopy (PROES) and particle-in-cell (PIC) simulations. Temporally asymmetric waveforms induce spatial asymmetries and offer control of the spatiotemporal dynamics of electron heating and associated ionization structures. Sawtooth waveforms with different rise and fall rates are employed using truncated Fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
120
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(125 citation statements)
references
References 27 publications
4
120
1
Order By: Relevance
“…23. A reactor with an inter-electrode gap of 2.5 cm was made geometrically symmetric by adding a thick Teflon ring (inner diameter 10 cm), fitted with a 2.5 Â 2.5 Â 10 cm piece of borosilicate glass to allow optical access.…”
Section: B Experimentsmentioning
confidence: 99%
See 3 more Smart Citations
“…23. A reactor with an inter-electrode gap of 2.5 cm was made geometrically symmetric by adding a thick Teflon ring (inner diameter 10 cm), fitted with a 2.5 Â 2.5 Â 10 cm piece of borosilicate glass to allow optical access.…”
Section: B Experimentsmentioning
confidence: 99%
“…Although the impact of the amplitude and slope asymmetry of a waveform has been studied in detail in argon discharges, [6][7][8][9][10][11][12][21][22][23] only one article by Schulze et al 25 has looked at the effect of TVWs on CF 4 discharges, and it is briefly studied in an article by Bruneau et al 26 The former study contained only simulations with no experimental measurements and was limited to two harmonics. Furthermore, there is an interest in studying the behavior of CF 4 discharges when excited with low fundamental frequencies, as used in etching applications.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This dual frequency (DF) excitation was previously investigated in low-pressure inductively coupled plasmas (ICPs) [18,19], capacitively coupled plasmas (CCPs) [20][21][22] and dielectric barrier discharges (DBDs) [23,24]. It was found that in low-pressure plasmas the LF and HF component can facilitate separate control of the ion energy and ion flux to the surface [19,20,25,26].…”
mentioning
confidence: 99%